'He Has Problems; He Is Not the Problem . . .' A Qualitative Study of Non-Custodial Staff Providing Services for Young Offenders Assessed for Foetal Alcohol Spectrum Disorder in an Australian Youth Detention Centre. (August 2019) - Hamilton, Sharynne L.; Reibel, Tracy; Watkins, Rochelle; Mutch, Raewyn C.; Kippin, Natalie R.; Freeman, Jacinta; Passmore, Hayley M.; Safe, Bernadette; O'Donnell, Melissa; Bower, Carol
Little is known about the challenges non-custodial youth detention centre staff face supporting young people with foetal alcohol spectrum disorder (FASD). We undertook qualitative inquiry to identify and describe the perspectives of non-custodial staff detention staff regarding the value of an FASD prevalence study. Data were collected using semi-structured interviews and focus groups and analysed using thematic network analysis. Staff held few concerns about the prevalence study and its impact on participating young people; however, they identified barriers related to study processes, and practices and culture within their workplace, which hindered gaining maximum benefit from the research and its findings.